The Influence Of Social Media, Price and Promotion on Online Product Purchase Decisions in E-Commerce - Ajy, Ismail Pangestu; Widodo, Agustina (Universitas Ibn Khaldun Bogor, 2023)
The purpose of this research is to show the effect of social media, price and promotion as factors that influence product purchasing decisions online in e-commerce (a case study on online shopping consumers at YPPI University students in Rembang). This study uses independent variables, namely social media, prices and promotions, the dependent variable is purchasing decisions. Data collection techniques were carried out in this study using a questionnaire. The data sources used in the research were primary data sources obtained from research instruments in the form of questionnaires filled out by respondents who distributed questionnaires online via the Google form. The population of this study consisted of YPPI Rembang University students who had shopped online at e-commerce. The sampling technique used in this research is accidental sampling. Based on the research results obtained, social media has a significant positive effect on purchasing decisions, price has a significant positive effect on purchasing decisions, promotion has an insignificant positive effect on purchasing decisions